Mechanisms of action of the antidiabetic peptide [S4K]CPF-AM1 in db/db mice. (February 2021) - Musale, Vishal; Moffett, R Charlotte; Owolabi, Bosede; Conlon, J Michael; Flatt, Peter R; Abdel-Wahab, Yasser H A
Abstract : The antidiabetic effects and mechanisms of action of an analogue of a frog skin host-defence peptide belonging to the caerulein-precursor fragment family, [S4K]CPF-AM1 were investigated in db/db mice with a genetically inherited form of degenerative diabetes-obesity. Twice-daily treatment with the peptide (75 nmol/kg body weight) for 28 days significantly decreased blood glucose ( P < 0.01) and HbA1c ( P < 0.05) and increased plasma insulin ( P < 0.05) concentrations with no effect on body weight, energy intake, body composition or plasma lipid profile. Peptide administration improved insulin sensitivity and intraperitoneal glucose tolerance. Elevated biomarkers of liver and kidney function associated with the db/db phenotype were significantly lowered by [S4K]CPF-AM1 administration. Peptide treatment significantly ( P < 0.05) increased pancreatic insulin content and improved the responses of isolated islets to established secretagogues. Elevated expression of genes associated with insulin signalling ( Slc2a4, Insr, Irs1, Akt1, Pik3ca, Ppm1b ) in the skeletal muscle of db/db mice were significantly downregulated by peptide treatment. Genes associated with insulin secretion ( Abcc8, Kcnj11, Slc2a2, Cacn1c, Glp1r, Gipr ) were significantly upregulated by treatment with [S4K]CPF-AM1. Studies with BRIN-BD1I clonal β-cells demonstrated that the peptide evoked membrane depolarisation, increased intracellular Ca 2+ and cAMP and activated the protein kinase C pathway. The data indicate that the antidiabetic properties of [S4K]CPF-AM1 mice are mediated by direct insulinotropic action and by regulation of transcription of genes involved in both the secretion and action of insulin.